The Blue Flower - Van Dyke, Henry, 1852-1933 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Blue Flower" by Henry Van Dyke is a collection of interconnected stories written in the early 20th century. The book explores the theme of the quest for happiness and meaning in life, symbolized by the elusive Blue Flower, through the eyes of various characters, notably a young boy and later, a traveler. These narratives weave together elements of nostalgia, introspection, and a longing for beauty, as they reflect on deeper truths amid life$1 (Bs mundane moments. The opening of the book introduces a boy who is captivated by the idea of a mysterious Blue Flower that represents his longing for something greater than the life he knows. As he dreams, he envisions a radiant flower in a tranquil setting, filled with light and beauty, illustrating his deep inner yearning. The scene shifts to a narrative about the Land of the Half-forgotten, where a solitary traveler seeks the secret of happiness. Through these early passages, Van Dyke sets a lyrical tone, hinting at the continuous search for fulfillment and the transformative power of imagination and dreams. The boy's dreams foreshadow the adventures that await him on his quest for the Blue Flower, establishing a poetic framework for the stories that follow. (This is an automatically generated summary.)s
The blue flower - The source -- The mill -- Spy rock -- Wood-magic -- The other wise men -- A handful of clay -- The lost word -- The first Christmas-tree.
Release date is 1999-01-01
Produced by An Anonymous Volunteer, and David Widger
Keywords: Fiction; Short stories